Πότε τα χαρισματικά παιδιά παρουσιάζουν χαμηλή επίδοση; - Γάκη Ανδρονίκη; Αντωνίου Αλέξανδρος-Σταμάτιος (Πανελλήνιο Συνέδριο Επιστημών Εκπαίδευσης, 2017)
The purpose of this chapter is to outline the phenomenon of low performance often seen in the training of charismatic children. In particular, charisma is considered to be the ability of the child to achieve a particularly high performance in one or more areas and is usually perceived as an asynchronous development between his cognitive, emotional and biological development. "Under-performance" means a student’s low performance, which runs counter to his / her mental potential and the potential that this entails. In fact, it is a mismatch between possibilities and performance and refers to the pupil’s image, which while having the potential, but the results of his effort are not the expected ones. The causes are attributed to the different way of learning adopted by charismatic children, to their desire to be accepted by their peers, while the family environment also plays an important role. For this reason, the role of the educator, who must be aware of the importance of timely intervention and of using the appropriate educational methods for the integration of the child into the group, is important.